Recovery of drug residues in equipment and utensils used by compounding pharmacies after standard cleaning procedure - Tassia Prioste; Thiago Ferreira dos Santos Magon; Vinicius Fagundes; Maiara Camotti Montanha; Cristiane Moriwaki; Elza Kimura (Universidade de São Paulo, 2015)
Compounding pharmacies have been cited by some athletes as being responsible for compounding capsules contaminated with drugs banned by the International Olympic Committee (IOC). Therefore, the present study was carried out to quantify the amount of residue remaining in the equipment and utensils used for compounding capsules after standard cleaning procedures. For this purpose, captopril (CAP) and acetylsalicylic acid (ASA) were used since these are hard to clean, in addition to hydrochlorothiazide (HTZ) as a banned drug by the IOC. The amounts of residues found in the equipment were: 181.0 ± 91.8, 1208 ± 483.8 and 431.7 ± 71.3 ppm for ASA, CAP and HTZ, respectively. The continuous compounding of these drugs, followed each time by the standard cleaning procedure, showed a linear accumulation of residues for ASA (r2=0.96) and CAP (r2= 0.88). The residues quantified were greater than the FDA limit for impurities for CAP (>0.1%) but not for HTZ. However, the HTZ residue may be detected in the urine of athletes on IOC tests. Therefore, it was concluded that compounding pharmacies should therefore improve their cleaning procedures and test these in order to attain limits below 10 ppm, thereby avoiding the contamination of other products.